About Some Persian Compound Words in Alisher Navoi’s Poem "Saddi Iskandari" - Alimova Zarifa Vaxobovna (Zien Journals, 2023)
This article talks about Persian compound words used in Alisher Navoi's poem "Saddi Iskandari". The etymological features of the Persian compound words in the work, their lexical meanings, the fact that they are based on comments in the Persian-Tajik dictionaries, the comparison with the comments given in other sources, scientific views on the lexical meanings of Persian words in the annotated dictionary of Navoi's works are given. The lexical and semantic meanings of the Persian compound words presented in the article are explained, they are grouped according to the expression of the profession and the expression of the action or state.
Keywords: compound words; sound change; metathesis; contact metathesis